Effects of Stigma on the Psychological Wellbeing of Hiv-positive Patients at Nsambya Homecare - Joan Deborah Acan (Ugnada Christian University, 2024)
This study investigates the effects of stigma on the psychological well-being of HIV-positive patients receiving care at Nsambya Homecare. Stigma associated with HIV/AIDS can significantly impact mental health influencing various dimensions of psychological well-being. Using a mixed-methods approach including surveys and in-depth interviews the research examines the relationship between perceived stigma and psychological outcomes such as depression, anxiety, and overall life satisfaction among patients. Quantitative data were collected through validated scales assessing stigma and psychological well-being while qualitative data were gathered through interviews exploring personal experiences and coping mechanisms. Findings reveal a significant association between high levels of stigma and poorer psychological well-being with affected individuals reporting increased levels of depression and anxiety. The study highlights the critical need for targeted interventions to address stigma and improve mental health support for HIV-positive patients. Recommendations include enhancing stigma reduction programs, providing psychological support services and fostering an inclusive environment at healthcare facilities to better support the mental health of individuals living with HIV. The study concludes that stigma has a profound negative impact on the psychological well-being of HIV-positive patients at Nsambya Homecare. High levels of stigma are significantly correlated with increased psychological distress including heightened depression and anxiety. These findings underscore the urgent need for comprehensive stigma reduction strategies and enhanced mental health support within healthcare settings. By addressing stigma and providing targeted psychological interventions healthcare providers can improve the overall well-being of HIV-positive individuals fostering a more supportive and inclusive environment for their care and treatment.